Studi Kualitatif Pencegahan dan Penanggulangan Bahaya Kebakaran di Lingkungan Kerja PT. Donggi Senoro LNG - Samrain, Samrain; Musdalifah, Musdalifah; Alim, Andi; Badwi, Adam (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2024)
Fires can be caused by errors or unsafe behaviour from humans and conditions in the workplace. To reduce/minimize losses, it is necessary to take preventive measures followed by security measures for the industry itself and its employees. Digging in-depth information about the readiness of PT. Donggi Senoro LNG in preventing and overcoming fire hazards. This research uses a qualitative descriptive approach, which describes efforts to prevent and control fires as early anticipation of fire hazards. This study found that the company committed to the Site Crisis Management Plan procedure, an emergency response organization, emergency response diagrams and a Safety Leadership Conversation (SLC) system. The availability of fire extinguishing facilities includes a Light Fire Extinguisher, hydrant & hose box, deluge valve system, and a fire engine. In addition, the company also has a fire fighting team that has been formed, carries out training or training activities and has work permits and other businesses. This study concluded that fire extinguishers that are exposed to direct sunlight should be made of a metal cover that can withstand hot and rainy weather. Suggestion: Carry out basic fire fighting training activities, especially for new employees. Keywords : Commitment, Fire Fighting Facilities, Training Or Training, Fire Fighting Team, Work Permit